Initial 1000-day experience of newly established public-funded pediatric cardiac care centre in low-middle income country - Pradeep Kumar Jain; Vivek Kumar Athwani; Kuber Sharma; Nimish Rai (Heart India)
Background: Comparing the burden of cardiac diseases in children, the availability of pediatric cardiac care (PCC) services is very dismal in our country. Timely management not only decreases mortality but also relieves the immense economic and social burden associated with these diseases. Establishing a PCC center in a resource-limited area is very challenging. In this study, we shared the experience of the successful establishment of a public funded PCC center in Central India and outcome of various procedures performed. Materials and Methods: We retrospectively reviewed data of various pediatric cardiac procedures performed in our newly established center from January 2020 to January 2023. Patients’ demographic profile, clinical profile, investigations, procedures done, and their success/failure/complications were noted and described. We have addressed challenges and explored solutions relating to patient care. Results: A total of 2034 pediatric patients with cardiac lesions and adults with congenital heart defects were included. Out of total 211 procedures, 165 were percutaneous interventional procedures (38 diagnostic and 127 therapeutic) and the rest 46 were open heart surgeries. The success rate in diagnostic procedures was 100%, while in therapeutic percutaneous interventional procedure and open heart surgeries, success rate was 93% and 91.3%, respectively. Conclusion: Establishing a successful PCC center even in resource-limited areas like ours is possible by fulfilling some key requirements. The outcomes of various procedures performed at our center were comparable to other established PCC centers.